Mucosal affairs: glycosylation and expression changes of gill goblet cells and mucins in a fish–polyopisthocotylidan interaction - Riera-Ferrer, Enrique; Del Pozo, Raquel; Muñoz-Berruezo, Uxue; Palenzuela, Oswaldo; Sitjà-Bobadilla, Ariadna; Estensoro, Itziar; Piazzon, M. Carla (Frontiers in Veterinary Science, 2024)
Secreted mucins are highly O-glycosylated glycoproteins produced by goblet cells in mucosal epithelia. They constitute the protective viscous gel layer overlying the epithelia and are involved in pathogen recognition, adhesion and expulsion. The gill polyopisthocotylidan ectoparasite Sparicotyle chrysophrii, feeds on gilthead seabream (Sparus aurata) blood eliciting severe anemia. Control unexposed and recipient (R) gill samples of gilthead seabream experimentally infected with S. chrysophrii were obtained at six consecutive times (0, 11, 20, 32, 41, and 61 days post-exposure (dpe)). In histological samples, goblet cell numbers and their intensity of lectin labelling was registered. Expression of nine mucin genes (muc2, muc2a, muc2b, muc5a/c, muc4, muc13, muc18, muc19, imuc) and three regulatory factors involved in goblet cell differentiation (hes1, elf3, agr2) was studied by qPCR. In addition, differential expression of glycosyltransferases and glycosidases was analyzed in silico from previously obtained RNAseq datasets of S. chrysophrii-infected gilthead seabream gills with two different infection intensities. Increased goblet cell differentiation (up-regulated elf3 and agr2) leading to neutral goblet cell hyperplasia on gill lamellae of R fish gills was found from 32 dpe on, when adult parasite stages were first detected. At this time point, acute increased expression of both secreted (muc2a, muc2b, muc5a/c) and membrane-bound mucins (imuc, muc4, muc18) occurred in R gills. Mucins did not acidify during the course of infection, but their glycosylation pattern varied towards more complex glycoconjugates with sialylated, fucosylated and branched structures, according to lectin labelling and the shift of glycosyltransferase expression patterns. Gilthead seabream gill mucosal response against S. chrysophrii involved neutral mucus hypersecretion, which could contribute to worm expulsion and facilitate gas exchange to counterbalance parasite-induced hypoxia. Stress induced by the sparicotylosis condition seems to lead to changes in glycosylation characteristic of more structurally complex mucins.